2015
DOI: 10.1016/j.celrep.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like 4 Increases Pulmonary Tissue Leakiness and Damage during Influenza Pneumonia

Abstract: Excessive host inflammatory responses negatively impact disease outcomes in respiratory infection. Host-pathogen interactions during the infective phase of influenza are well studied, but little is known about the host's response during the repair stage. Here, we show that influenza infection stimulated the expression of angiopoietin-like 4 (ANGPTL4) via a direct IL6-STAT3-mediated mechanism. ANGPTL4 enhanced pulmonary tissue leakiness and exacerbated inflammation-induced lung damage. Treatment of infected mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 29 publications
4
79
0
1
Order By: Relevance
“…In addition, ANGPTL4, which has been implicated in IAV infection (Li et al, 2015), was also among the validated antiviral factors. Furthermore, we identified CCL3L3, a cytokine that binds to several chemokine receptors, including CCR5, and acts as a chemotactic for lymphocytes and monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ANGPTL4, which has been implicated in IAV infection (Li et al, 2015), was also among the validated antiviral factors. Furthermore, we identified CCL3L3, a cytokine that binds to several chemokine receptors, including CCR5, and acts as a chemotactic for lymphocytes and monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the increased infiltration of immune cells and heightened inflammation did not cause increased cytotoxicity in T-bet À/À lungs as reflected by the level of lactate dehydrogenase (LDH) in the BAL (Fig 1E). To further assess tissue repair in T-bet À/À lungs, podoplanin (PDPN), a glycoprotein expressed on alveolar type 1 epithelial cells and marker of lung injury and repair (Li et al, 2015;Zuo et al, 2015), was stained by Western blot (Figs 1F and EV1D) and immunohistochemistry (Fig EV1E). To further assess tissue repair in T-bet À/À lungs, podoplanin (PDPN), a glycoprotein expressed on alveolar type 1 epithelial cells and marker of lung injury and repair (Li et al, 2015;Zuo et al, 2015), was stained by Western blot (Figs 1F and EV1D) and immunohistochemistry (Fig EV1E).…”
Section: T-bet à/à Mice Clear Influenza Virus Infection With Increasementioning
confidence: 99%
“…We chose ANGPTL4 for further analysis, because its expression could be induced by acute phase response [31]. Liang et al [32] showed that influenza infection could stimulate the expression of ANGPTL4, and treatment of infected mice with neutralizing anti-ANGPTL4 antibodies significantly accelerated lung recovery and improved lung tissue integrity. Moreover, ANGPTL4-deficient mice also showed reduced lung damage and recovered faster from influenza infection when compared to their wild-type counterparts.…”
Section: Discussionmentioning
confidence: 99%